2010
DOI: 10.3168/jds.2009-2645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of rumen-protected conjugated linoleic acid to grazing cows in early lactation

Abstract: Conjugated linoleic acids (CLA) are potent anticarcinogens in animal and in vitro models as well as inhibitors of fatty acid synthesis in mammary gland, liver, and adipose tissue. Our objective was to evaluate long-term CLA supplementation of lactating dairy cows in tropical pasture on milk production and composition and residual effects posttreatment. Thirty crossbred cows grazing stargrass (Cynodon nlemfuensis Vanderyst var. nlemfüensis) were blocked by parity and received 150 g/d of a dietary fat supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
5
25
1
11
Order By: Relevance
“…Despite the reduction in milk fat content with the triggering of these physiological processes at the expense of higher concentrations of CLA trans-10, cis-12, some studies (Bernal-Santos et al, 2003;Selberg et al, 2004;Medeiros et al, 2010) have shown that this reduction has benefits on the negative energy balance (NEB) by decreasing the energy content excreted in milk, and this favors the increase in the amount of energy retained in the animal body, which in turn reduces the mobilization of body reserves. This is consistent with the data obtained in this study, because the group of cows on the CS diet presented less intense NEB in the transition period (40.32%) in relation to the SO diet, and about 20.0% lower in relation to the animals subjected to diet C, demonstrating the beneficial effect on energy partition (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduction in milk fat content with the triggering of these physiological processes at the expense of higher concentrations of CLA trans-10, cis-12, some studies (Bernal-Santos et al, 2003;Selberg et al, 2004;Medeiros et al, 2010) have shown that this reduction has benefits on the negative energy balance (NEB) by decreasing the energy content excreted in milk, and this favors the increase in the amount of energy retained in the animal body, which in turn reduces the mobilization of body reserves. This is consistent with the data obtained in this study, because the group of cows on the CS diet presented less intense NEB in the transition period (40.32%) in relation to the SO diet, and about 20.0% lower in relation to the animals subjected to diet C, demonstrating the beneficial effect on energy partition (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Os teores médios de lactose, em trabalhos conduzidos em pasto com suplementação, variaram de 4,51 a 5, 10 (SCHROEDER et al, 2002;MEDEIROS et al, 2010). Estes valores são superiores aos encontrados no presente estudo, onde não houve diferença (P>0,05) entre os níveis de concentrado.…”
Section: Resultsunclassified
“…Trabalhando com animais terminados em pastagens tropicais Padre et al (2006) observaram valor médio de CLA de 0,14%, inferiores ao encontrados no presente estudo. Medeiros et al (2010) justificam o menor conteúdo de CLA em animais alimentados com forrageira tropical perante os animais confinados pelos menores teores de ácido linolênico e maiores de palmítico (Tabela 2) que essas forrageiras apresentam. Esse perfil seria menos favorável a produção de CLA, fato que não foi observado no presente estudo.…”
Section: Houve Variação No Teor Lipídico Do Músculounclassified
“…Pelas supostas implicações positivas dos ácidos graxos ω-3 na saúde humana, a maior concentração, normalmente encontrada, seria uma vantagem na produção de animais a pasto. No entanto, a transferência dessa conclusão para os animais a pasto em países tropicais, em função da grande diferença de perfil de ácidos graxos entre forrageiras tropicais e temperadas, é prematura (MEDEIROS et al, 2010).…”
Section: Introductionunclassified